Stalagmite-inferred centennial variability of the Asian summer monsoon in southwest China between 58 and 79 ka BP. (15th March 2017) - Zhang, Tao-Tao; Li, Ting-Yong; Cheng, Hai; Edwards, R. Lawrence; Shen, Chuan-Chou; Spötl, Christoph; Li, Hong-Chun; Han, Li-Yin; Li, Jun-Yun; Huang, Chun-Xia; Zhao, Xin
Abstract: We use a new spliced stalagmite oxygen isotope record from Yangkou Cave and Xinya Cave, Chongqing, southwest China, to reconstruct the centennial-millennial-scale changes in Asian Summer Monsoon (ASM) intensity between 58.0 and 79.3 thousand years before present (ka BP, before AD 1950). This multidecadally resolved record shows four strong ASM periods, corresponding to Greenland Interstadials (GIS) 17–20, and three weak ASM episodes, among which, the one starting at 61.5 ± 0.2 ka BP and ending at 59.4 ± 0.2 ka BP that may correlate with Heinrich Event 6. The close agreement of climate events between China and Greenland supports the notion that the ASM is dominantly governed by high-latitude forcings in the Northern Hemisphere. The short-lived interstadial GIS 18, however, lasted for over 3 kyr in the records derived from ASM region, reflecting a gradual decline of ASM intensity, which coincides with a millennial-scale warming trend in Antarctica. This suggests an additional forcing of the ASM by the Southern Hemisphere, which also affected GIS 8–12, H4 and H5, as shown by previous speleothem studies from the ASM region. Highlights: New chronology reference of series climatic events in MIS 4 based on new records of Chinese stalagmite. This is the first time that speleothem records from China recorded the gradual decline of ASM from D/O 18 to H6. Gradual decline of ASM from D/O 18 to H6, suggests an additional forcing of the ASM by the Southern Hemisphere.